2008
DOI: 10.1002/jat.1382
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cytotoxic and inflammatory responses of photoluminescent silicon nanoparticles with silicon micron‐sized particles in RAW 264.7 macrophages

Abstract: Photoluminescent silicon nanoparticles have a bright and stable fluorescence and are promising candidates for bio-imaging, cell staining and drug delivery. With increasing development of nanotechnology applications for biomedicine, an understanding of the potential toxicity of nanoparticles is needed to assess safety concerns for clinical applications. The objective of this study was to compare biological responses of silicon nanoparticles (SNs, 3 nm diameter) with silicon microparticles (SMs, approximately 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 40 publications
5
77
0
Order By: Relevance
“…59 Choi et al showed, for example, that silicon nanoparticles are more cytotoxic than larger silicon microspheres due to differences in the specific surface area, the number of particles at the equivalent gram concentration and the internalization pathway. 60 The cytotoxicity of silver is highly dependent on its concentration: within a defined therapeutic window it has antimicrobial properties but does not affect mammalian cells, making it an effective antibacterial agent. 14 We show here that neither SiO 2 nanocontainers nor Ag@SiO 2 nanorattles affect the viability of dendritic cells except at the highest concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…59 Choi et al showed, for example, that silicon nanoparticles are more cytotoxic than larger silicon microspheres due to differences in the specific surface area, the number of particles at the equivalent gram concentration and the internalization pathway. 60 The cytotoxicity of silver is highly dependent on its concentration: within a defined therapeutic window it has antimicrobial properties but does not affect mammalian cells, making it an effective antibacterial agent. 14 We show here that neither SiO 2 nanocontainers nor Ag@SiO 2 nanorattles affect the viability of dendritic cells except at the highest concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…According to study results, HaCaT cells lines exposed to SiO (2) NPs showed cytotoxicity in a concentrationdependent and time-dependent manner (Gong et al 2012). In a research conducted on murine macrophages (RAW 264.7), Choi et al (2009) found that silicon NPs increased the cytotoxicity. Again, the results also support the observations of Yang et al (2010), who have showed that exposure of HaCaT cells to 15-nm and 30-nm SiO 2 particles resulted in significantly decreased cell viability in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the toxicological studies in this field have been focused on a few nanoparticles used either as health products, such as iron oxide (15,17,22), or in a variety of consumer products, such as silver (13,14), silica (9,12), and titanium dioxide (11,16,20,21).…”
Section: Teins (Especially Oxidative Phosphorylation Complex Subunitsmentioning
confidence: 99%